Fifth generation wars and their impact on international peace and security: "The Russian-Ukrainian war as a model" - Bourouihiya, Badr Abdellah (Journal of Economic, Administrative and Legal Sciences, 2024)
In the face of a multitude of security threats confronting major powers, compounded by the blurred demarcation lines between domestic, regional, and international spheres, a series of consecutive regional and international crises has magnified the repercussions on international peace and security. The advancement of military capabilities has played a role in giving rise to novel military concepts and theories that have emerged from the realm of unconventional security threats, which have come to the forefront of the global arena over the past two decades. This has consequently led to the dissemination of terminologies such as "internal wars," "proxy wars," "asymmetric warfare," "cyber warfare," and "cybersecurity warfare," among other types of warfare that often serve as direct triggers for conventional military conflicts. This has precipitated the emergence of a new breed of warfare known as "Fifth-Generation Warfare." This paradigm of warfare finds vivid illustration in the context of the Russian-Ukrainian conflict, where the principles of Fifth-Generation Warfare are conspicuously evident. As the landscape of security threats continues to evolve, it becomes imperative for international stakeholders to recalibrate their strategies in order to effectively counter these emerging challenges and uphold global stability.